Optimization of Professional Zakat Fund Management at the Office of Ministry of Religion of Parepare City - Usman, M. Hasyim; Hannani, Hannani; Muchsin, Agus (IAIN Parepare, 2020)
Poverty is a problem faced by the Indonesian people and is the responsibility of the Indonesian government. The approach used in this study is the theological, penomenological, and juridical approaches. The source of this research data is sourced from primary and secondary legal materials. This research includes qualitative using data in the form of direct interviews and questions and answers or dialogues and documents. The data obtained are then collected both primary and secondary. Data collection techniques are carried out through observation, interviews and documentation studies in order to obtain clear and representative data, while data processing and analysis techniques are carried out through data reduction, data presentation and drawing conclusions. The results of this study indicate that the optimization of the management of professional zakat funds at Ministry of Religion Office,Parepare City is less than optimal. However, in terms of collection has fulfilled the principles of sharia, trustworthiness, transparency, professionalism, accountability, participation and efficiency. Its distribution is still traditional and productive productive creative and not in accordance with the principles of justice.